Control of immune cell signaling by the immuno-metabolite itaconate - Lang, Roland; Siddique, Md Nur A Alam (Frontiers in Immunology, 2024)
Immune cell activation triggers signaling cascades leading to transcriptional reprogramming, but also strongly impacts on the cell’s metabolic activity to provide energy and biomolecules for inflammatory and proliferative responses. Macrophages activated by microbial pathogen-associated molecular patterns and cytokines upregulate expression of the enzyme ACOD1 that generates the immune-metabolite itaconate by decarboxylation of the TCA cycle metabolite cis-aconitate. Itaconate has anti-microbial as well as immunomodulatory activities, which makes it attractive as endogenous effector metabolite fighting infection and restraining inflammation. Here, we first summarize the pathways and stimuli inducing ACOD1 expression in macrophages. The focus of the review then lies on the mechanisms by which itaconate, and its synthetic derivatives and endogenous isomers, modulate immune cell signaling and metabolic pathways. Multiple targets have been revealed, from inhibition of enzymes to the post-translational modification of many proteins at cysteine or lysine residues. The modulation of signaling proteins like STING, SYK, JAK1, RIPK3 and KEAP1, transcription regulators (e.g. Tet2, TFEB) and inflammasome components (NLRP3, GSDMD) provides a biochemical basis for the immune-regulatory effects of the ACOD1-itaconate pathway. While the field has intensely studied control of macrophages by itaconate in infection and inflammation models, neutrophils have now entered the scene as producers and cellular targets of itaconate. Furthermore, regulation of adaptive immune responses by endogenous itaconate, as well as by exogenously added itaconate and derivatives, can be mediated by direct and indirect effects on T cells and antigen-presenting cells, respectively. Taken together, research in ACOD1-itaconate to date has revealed its relevance in diverse immune cell signaling pathways, which now provides opportunities for potential therapeutic or preventive manipulation of host defense and inflammation.